P3_7 Why Does Venus Spin Backwards? - Harvey, Max; Harding, Ben; Acton, Jack; Kneebone, Ricky (Physics Special Topics, 2017)
Venus has a very slow, retrograde rotation compared to the 24 hour prograde rotations of Earth and Mars. We find that for an impacting asteroid to have changed Venus' rotation from an Earth-like period and direction to its current state, a minimum asteroid mass of 2x10^29kg would be required, and that such a collision would destroy Venus. This makes it unlikely that such a collision is responsible for the odd Venusian rotation.